2008
DOI: 10.1109/joe.2008.923554
|View full text |Cite
|
Sign up to set email alerts
|

Robust Nonlinear Path-Following Control of an AUV

Abstract: International audienceThis paper develops a robust non-linear controller that asymptotically drives the dynamic model of an AUV onto a predefined path at a constant forward speed. A kinematic controller is first derived, and extended to cope with vehicle dynamics by resorting to backstepping and Lyapunov-based techniques. Robustness to vehicle parameter uncertainty is addressed by incorporating a hybrid parameter adaptation scheme. The resulting nonlinear adaptive control system is formally shown and yields as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(121 citation statements)
references
References 12 publications
0
113
0
1
Order By: Relevance
“…The Nonlinear Control Based (NCB) path following controller, has its grounds on the work done in [9], [10] on path following control for kinematic models of wheeled mobile robots and in [17], [22] on the same topic but for autonomous underwater vehicles. In contrast to the work described in [9], the usage of the virtual target principle enables the formulation of the path following problem in a non-singular manner, thus guaranteeing global convergence to the path.…”
Section: Nonlinear Based Controllermentioning
confidence: 99%
“…The Nonlinear Control Based (NCB) path following controller, has its grounds on the work done in [9], [10] on path following control for kinematic models of wheeled mobile robots and in [17], [22] on the same topic but for autonomous underwater vehicles. In contrast to the work described in [9], the usage of the virtual target principle enables the formulation of the path following problem in a non-singular manner, thus guaranteeing global convergence to the path.…”
Section: Nonlinear Based Controllermentioning
confidence: 99%
“…Robust controllers are well known for their immunity to disturbances, and have been widely used in underwater vehicles [5,11,16]. Robust terms were often employed to handle the approximation errors of neural networks, external disturbances, and estimation errors of adaptive controllers.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of disturbance caused by wave-induced hydrodynamic forces, Patompak and Nilkhamhang provided an adaptive backstepping sliding mode controller for station keeping and path following of underwater vehicle based on its dynamic model [11]. Lapierre and Jouvencel extended a kinematic controller with backstepping and Lyapunov-based techniques so as to cope with parametric uncertainties and external disturbances [12]. The controllers shown in [13][14][15] confirmed that the model-based backstepping controller outperforms the conventional linear controller for the wide range of velocities.…”
Section: Introductionmentioning
confidence: 99%